Human Rights in Asia - Davis, Thomas W. D.; Galligan, Brian 1945- (Edward Elgar, 2011)
"This book presents the work of a dozen scholars from Asia and Australasia and draws upon their knowledge of particular countries or aspects of the politics of rights that help in understanding rights in Asia. Most of the contributors participated in an international symposium held at the University of Melbourne in late 2009, with several who could not attend also contributing papers."-- P. xiii.